Experimental study on pressure sensitive properties of copper contaminated soil solidified by modified red mud - Shen, Keyu (Journal of Environmental Engineering and Landscape Management, 2019)
As a static method for testing pollution and strength of soil, the resistivity method has been used by many scholars, whereas few studies have been carried out on dynamic deformation monitoring by this method. To study the pressure sensitive properties of copper contaminated soils solidified by modified red mud, a series of unconfined compression tests were conducted. The compressive stress, strain and electrical resistivity in whole process were determined. Relationship between the resistivity and the parameters including stress, strain, red mud content, copper content, and curing age were analysed. Then the mechanism of electrical resistivity is revealed. Results indicate the stress-resistivity change rate follows the same trend as the stress-strain curve. The resistivity change rate follows the same rule as the strain change, indicating that the electrical resistivity can reflect the strain indirectly. The higher red mud content is, the better pressure sensitive properties of solidified soil is. A proper amount of copper can improve the pressure sensitivity of solidified soil, while excessive copper ions can reduce pressure sensitivity of solidified soil. These changes can be attributed to the pore water, iron oxide in red mud, tunnel conductive effect and conductivity percolation.